Addiction to tobacco smoking and vaping - Andrea Hernández-Pérez; Leonor García-Gómez; Robinson Robles-Hernández; Ireri Thirión-Romero; Jennifer Osio-Echánove; Sebastián Rodríguez-Llamazares; Ruben Baler; Rogelio Pérez-Padilla (Permanyer, 2023)
The tobacco epidemic has been one of the biggest public health threats, and smoking is one of the world's largest preventable causes of premature death. An estimated 15.4% of all deaths in the world are attributable to tobacco smoking. The present review aims to describe addiction to tobacco smoking and vaping. Tobacco and vaping devices contain nicotine, a highly addictive drug, which explains why smoking is so prevalent and persistent. Electronic cigarettes are a group of novel nicotine or tobacco products that have rapidly gained popularity in recent years. Electronic cigarette devices allow for the use of other drugs, including THC, while the lax regulation may allow for the introduction of toxic compounds that can lead to acute or subacute toxicity, such as the e-cigarette- or vaping-associated lung injury that has been linked to vitamin E acetate. In addition, regular vapers and heated tobacco devices emit toxins, although at lower concentrations than burned tobacco. However, more and more side effects have been identified. No new effective treatment for nicotine addiction has been developed recently, despite its huge adverse impact on overall health and other outcomes. As for the primary line of medications, the last one started in 2006, the varenicline, demonstrating a low interest in developing new medications against smoking, an unacceptable state of affairs, given the huge impact of smoking on morbidity and mortality.